Pottery conveyance in North Patagonia, Argentina: Implications for human mobility across the region. (February 2020) - Sugrañes, Nuria; Neme, Gustavo; Glascock, Michael D.; Eerkens, Jelmer; Lee MacDonald, Brandi
Abstract: The introduction of pottery in North Patagonia (Argentina), approximately 2000 years BP, allowed hunter-gatherers to exploit resources in new ways, but also required alterations to lifeways to accommodate this new technology, especially in territoriality, exchange, and home ranges. Ceramic provenance analysis allows us to focus on the characteristics of pot circulation and conveyance in the region. In this paper, we explore the topic applying neutron activation analysis to ceramic sherds from six archaeological sites distributed in the Atuel river basin, from Northern Patagonia (Argentina) (Fig. 1). Results show a minimum of six distinctive compositional groups spread in a non-random fashion across the six sites. The distribution suggests a restricted circulation of selected ceramic vessels between two different environments -- highlands vs. lowlands-- that may be related to the exploitation of complementary resources in those contexts. We interpret the compositional data as a reflection of how ceramic technologies were embedded in a residentially mobile settlement pattern. Groups may have produced ceramic vessels ("geared up") in one location and brought them to other locations during short-term visits to exploit locally abundant resources.